X-ray spectroscopy and imaging of selenium in living systems - Dolgova, Natalia V.; Nehzati, Susan; Choudhury, Sanjukta; MacDonald, Tracy C.; Regnier, Nathan R.; Crawford, Andrew M.; Ponomarenko, Olena; George, Graham N.; Pickering, Ingrid J. (Biochimica et biophysica acta. General subjects, 2018)
Selenium is an essential element with a rich and varied chemistry in living organisms. It plays a variety of important roles ranging from being essential in enzymes that are critical for redox homeostasis to acting as a deterrent for herbivory in hyperaccumulating plants. Despite its importance there are many open questions, especially related to its chemistry in situ within living organisms. This review discusses X-ray spectroscopy and imaging of selenium in biological samples, with an emphasis on the methods, and in particular the techniques of X-ray absorption spectroscopy (XAS) and X-ray fluorescence imaging (XFI). We discuss the experimental methods and capabilities of XAS and XFI, and review their advantages and their limitations. A perspective on future possibilities and next-generation of experiments is also provided. XAS and XFI provide powerful probes of selenium chemistry, together with unique in situ capabilities. The opportunities and capabilities of the next generation of advanced X-ray spectroscopy experiments are particularly exciting. XAS and XFI provide versatile tools that are generally applicable to any element with a convenient X-ray absorption edge, suitable for investigating complex systems essentially without pre-treatment. •Introduction of X-ray spectroscopy and imaging for biological selenium•Physical background: absorption of X-rays through core electron excitation•Advantages and limitations of selenium X-ray absorption spectroscopy•Selenium X-ray fluorescence imaging: 2D and 3D methods•Advanced spectroscopy and imaging: next-generation applications for future research